2022
DOI: 10.1002/ecs2.4271
|View full text |Cite
|
Sign up to set email alerts
|

Turning up the heat: Long‐term water quality responses to wildfires and climate change in a hypereutrophic lake

Abstract: Clear Lake (Lake County, CA, USA) is hypereutrophic and used for drinking water, tribal use, and supports a significant fishing economy. The Mendocino Complex (2018), one of the largest wildfires in California's post‐settlement history, burned 40% of the Clear Lake watershed, providing a timely opportunity to study the impacts of historical and current wildfires on this valuable aquatic resource. Using long‐term monthly monitoring data from 1968 to 2019, paired with historical watershed fire data, we found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…For example, mixed or weak algal biomass responses to wildfire may reflect bias toward high‐latitude regions with carbon‐rich soils. Moreover, wildfire‐derived nutrients may be negligible for highly productive lakes (De Palma‐Dow et al., 2022; Lewis et al., 2014). These studies suggest that clear, unproductive lakes could experience post‐wildfire increases in primary productivity, but also that post‐wildfire dynamics of nutrient and light limitation are important.…”
Section: Discussionmentioning
confidence: 99%
“…For example, mixed or weak algal biomass responses to wildfire may reflect bias toward high‐latitude regions with carbon‐rich soils. Moreover, wildfire‐derived nutrients may be negligible for highly productive lakes (De Palma‐Dow et al., 2022; Lewis et al., 2014). These studies suggest that clear, unproductive lakes could experience post‐wildfire increases in primary productivity, but also that post‐wildfire dynamics of nutrient and light limitation are important.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies investigating the effects of wildfires on lakes, post-fire changes in lake concentrations (i.e., nutrients) were not regularly observed. De Palma-Dow et al [27] did not find a substantial change in total phosphorous concentrations up to three years post-fire and found no changes in relation to smaller fires when analyzing Clear Lake (California), despite the very large burned area and its proximity to the lake (40% of the watershed burned at 1 km from the shoreline). A study of boreal Alaskan lakes [24] found that nutrient concentrations were not sensitive to wildfires up to two years after the event.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, some general patterns and responses of wildfire effects on water quality have emerged [27], including increased concentrations of nutrients, ions, organic material, and a general decrease in water clarity, following post-fire increments in erosion and runoff while changes in chlorophyll-a were less consistent [28]. A recent review of 44 studies worldwide [5] comparing pre-and post-fire water quality field sampling data found that wildfires increased post-fire nutrient export relative to pre-fire levels within a one-year time lag between sampling and fire occurrence.…”
Section: Introductionmentioning
confidence: 99%